Rigor by design, not chance : deeper thinking through actionable instruction and assessment - Hess, Karin (Karin K.) (ASCD, 2023)
"A practical and systematic approach to deepening student engagement, promoting a growth mindset, and building a classroom culture that truly supports thinking and learning"-- Provided by publisher.
Keywords: Cognitive learning.; Thought and thinking -- Study and teaching.; Educational tests and measurements.; Motivation in education.; Apprentissage cognitif.; Pensée -- Étude et enseignement.; Tests et mesures en éducation.; Motivation en éducation.; Cognitive learning; Educational tests and measurements; Motivation in education; Thought and thinking -- Study and teaching